Tindak Lanjut Hasil Asesmen Terhadap Pelaksanaan Pembelajaran Anak Usia Dini di Taman Kanak-Kanak (TK) - Reiska Primanisa; Nurul Zahriani Jf (Jurnal Pendidikan Raudhatul Athfal, 2020)
Follow-up on the results of the assessment of the implementation of early childhood learning in kindergarten (TK) is a research that aims to improve the quality of education such as improving the competence of educators, to improve children's abilities through collaboration with parents of students, as well as to improve the implementation of program planning more accurately, either making something new or modifying an existing one. The methodology of scientific articles based on the results of this study uses a literature study approach (Library Research), data collection techniques namely documentation methods, and for data analysis usingmethods content analysis. . The results of this study indicate that the follow-up results of the assessment contribute to PAUD educators in kindergarten as an effort of educators in order to conclude all children's activities as materials to improve the competence of PAUD educators, improve children's development abilities, and make planning learning programs that are even better going forward. So that the child's growth and development can be optimized according to the expectations and goals of education.